Characterization of carbon dots passivated with polyethylene glycol using UV spectroscopy and electron microscopy / Muhammad Kamil Khalid - Khalid, Muhammad Kamil (2014)
Recently, carbon dots has drawn wide attention of reseachers around the globe with their amazing properties such as great fluorescence properties, can be used in bioimaging aspect, non photobleaching, low toxicity and high stability. This research project is focused on the synthesis of carbon dots and its characterization using ultra-violet visible spectroscopy, transmission electron microscopy and scanning electron microscopy. Activated charcoal was used to prepare carbon dots by nitric acid reflux. The carbon dots that synthesized were characterized using UV spectroscopy, transmission electron microscopy and scanning electron microscopy. UV spectrum revealed the peak between 220nm and 320nm which indicates the presence of carbon dots. Transmission electron microscopy and scanning electron microscopy images shown carbon dots have average sizes less than 1 Onm and smooth surface respectively. Passivation with different types of polyethylene glycol produced different effect on absorbance of carbon dots. UV spectroscopic proves the effect of auxochrome which causes hyperchromic effect that is increase the UV absorbance of carbon dots when passivated with different type of polyethylene glycol.